CEO educational attainment, green innovation, and enterprise performance: Evidence from China’s heavy-polluting enterprises - Zhang, Chenyu; Li, Haoyu; Gou, Xiang; Feng, Jie; Gao, Xing (Frontiers in Environmental Science, 2022)
As the decision maker and executor, the education attainment of the chief executive officer (CEO) greatly influences the environmental innovation behaviour of enterprises. However, little study uses environmental patents in the patent database of listed companies to measure green innovation at micro-level. Furthermore, existing studies have little consideration on the heterogeneity of enterprise type, social responsibility and institutional intervention. Thus, based on the data of listed companies in heavily polluting industries in Shanghai and Shenzhen from 2010 to 2018, this study empirically examines the influence of CEOs’ education attainment on green innovation at enterprise level, and discusses whether CEO education attainment and green innovation will improve the enterprise performance. We find that there is a positive relationship between CEO education attainment and the green innovation. The result remains valid after controlling companies’ fixed effects and using the propensity score matching method (PSM) to eliminate endogenous and sample selection bias. Robust evidence still concludes: (1) The positive influence of CEOs’ education attainment on green innovation behaviour is more significant in private enterprises and enterprises with higher social responsibility. (2) Strict environmental legislation can improve the positive impact in regions with heavy environmental pollution. (3) Enterprises’ performance and sustainable environmental innovation will be promoted by the positive mechanism.